Empirical Study of Emotional Intelligence and Work Ethic among Bekasi Environmental Office Employees - Miftah Auliyah Sukma Putri; Anita Novialumi (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study investigates the impact of emotional intelligence and work ethic on the performance of State Civil Apparatus (ASN) at the Environmental Service Office of Bekasi City. Given the increasing demand for effective public service, understanding the role of non-technical factors in enhancing employee performance is essential. Methodology/approach: This research employs a quantitative approach, involving 126 operational employees as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS version 29. The study utilized non-probability sampling to select participants from the operations division. Results/findings: The results demonstrate that both emotional intelligence and work ethic have a statistically significant and positive influence on employee performance. This is evidenced by an F-value of 180.729 (Sig. = 0.001), indicating a strong combined effect of the two variables. Conclusion: Both of emotional intelligence and work ethic are critical determinants of ASN performance. Therefore, enhancing ASN performance requires more than technical competence; it necessitates the development of personal attributes and behavioral values that foster emotional regulation and ethical conduct. Limitations: This research is limited to operational employees of the Bekasi City Environmental Agency with a quantitative approach, and only includes variables of emotional intelligence and work ethic. The results cannot be generalized to other agencies or sectors. Contribution: Studies in human resource management that have focused on the impact of EQ and WORK ETHIC on productivity have benefited from this new data. In an attempt to boost ASN performance by enhancing emotional components and work ethic, these results are helpful for government organizations.